Unravelling the Contribution of Turbulence and Bubbles to Air-Water Gas Exchange in Running Waters - Klaus, Marcus; Labasque, Thierry; Botter, Gianluca; Durighetto, Nicola; Schelker, Jakob (Swedish University of Agricultural Sciences, 2021)
Aquatic ecosystems exchange gases with the atmosphere and this exchange is critical for many ecosystem processes and the global greenhouse gas cycle. However, it is difficult to determine how fast gases exchange with the atmosphere, especially in running waters where bubbles can speed up the exchange of certain gases. Here, we provide a data set on air-water gas exchange velocities, collected during an outdoor flume experiment. We used experimental stream channels to create a wide range of flow conditions, and tested how these conditions effect the rate at which different gases in the water exchange with the atmosphere. Besides gas exchange velocities for direct air-water exchange and exchange mediated by bubbles, the data set also contains data on, among others, flow conditions, turbulent kinetic energy dissipation rate, bubble flux rate and ambient underwater sound pressure signatures. The experimental design and data are described in articles by Vingiani et al. (2021) and Klaus et al. (2022).

main data contributions:
(1) Gas exchange velocity estimates based on mass balance of various gases in flume water
Concentrations of helium, xenon, argon och methane were measured in the in- and outlet water of the flumes using mass-spectrometry . A mass balance of the gases yielded air-water gas exchange velocities.
(2) turbulent kinetic energy dissipation estimates based on Acoustic Doppler Velocimetry
Three-dimensional flow velocities were measured at 24 locations per flume using an Acoustic Doppler Velocity meter. Spectral analysis was applied to derives turbulent kinetic energy dissipation rates.
(3) sound pressure signatures derived from Hydrophone and microphone recordings
Ambient sound was recorded at 12 locations per flume using a hydrophone and a microphone. Spectral analysis was used to derive sound signatures associated with water flow / turbulence and air bubbles.

Vattendrag bidrar med viktiga ekosystemtjänster till samhället och många av dessa processer är kopplade till vattendragens utbyte av gaser med atmosfären. Detaljerad kunskap om vilka processer som reglerar detta gasutbyte är dock bristfällig, framförallt rollen av bubblor som kan snabba på utbytet för vissa gaser. Den här databasen innehåller resultat från ett utomhusexperiment i rännor. Vi simulerade ett brett spektrum av flödesförhållanden i dessa rännor och undersökte hur dessa förhållanden påverkar hur snabbt olika gaser släpps från vattnet till atmosfären. Databasen innehåller resultat på gasutbyteshastigheten både för det direkta utbytet mellan vattnet och atmosfären, och det indirekta utbytet genom bubblor. Dessutom finns resultat på bland annat turbulens-, flödes-, och ljudförhållanden i rännorna. Den experimentella designen och datat beskrivs i artiklar av Vingiani et al. (2021) och Klaus et al. (2022).

huvudsakliga datakällor/metoder:
(1) gasutbyteshastigheter tagit fram genom massbalansberäkningar i rännorna
Koncentrationer av helium, xenon, argon och metan har mätts i in- och utloppsvattnet i rännorna med en masspektrometer. en massbalans av gaserna har gjorts för att ta fram gasutbyteshastigheter med atmosfären.
(2) turbulens beräknat från tredimensionella flödesmätningar
Tredimensionella flödeshastigheter har mätts vid 24 punkter per ränna med en Akustiskt Doppler Velocitymeter och spektralanalys har använts för att beräkna turbulens.
(3) ljudtryck mätt med hydrofoner och mikrofoner
Ljud har spelats in vid 12 punkter per ränna med hydrofoner och mikrofoner och spektralanalys har använts för att ta fram ljudsignaturer skapat av vattenflödet/turbulens och bubblor.
Kvantifiering av bidrag av turbulens och bubblor till gasutbyte i vattendrag
EXSONIC
Keywords: TURBULENCE; SOUNDS; DISCHARGE/FLOW; gas; gas; model; modell; watercourse; vattendrag; Bubble; Bubbla; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Geoscientific Information; Geovetenskap; Inland Waters; Sjöar och vattendrag